Improving the tools continuing to look for improvements in the design and production of the pole vault pole - Warty, J. (3rd European Pole Vault Conference - Köln 2008, 2008)
Jeff Warty (Pacer-Gill) gave insight on modern pole production methods used to generate world class vaulting poles. Trying to further develop modern vaulting poles into the future, Pacer is using sophisticated ways to choose, store and test the best suited materials, constantly improving the process of designing and producing safe high performance poles. The ultimate goal is to produce the right pole for every individual vaulter.